Fasting reduces satiety and increases hunger but does not affect the performance in resistance training - Drummond, Marcos D.M.; Soares, Paula S.G.; Savoi, Lucas A.; Silva, Ronaldo A.D. (Biology of Sport, 2024)
Intermittent fasting (IF) has been suggested to reduce body fat percentage and improve noncommunicable chronic diseases. However, little is known about resistance training (RT) and the subjective perception of hunger under fasted conditions. This study aimed to examine the effects of overnight fasting (12 h or 16 h fasting) on the maximum voluntary isometric contraction (MVIC) and countermovement jump (CMJ) performance in resistance trained young male adults. In RT sessions, the maximum number of repetitions (MNR) and the total volume load (TVL) were evaluated in the back squat and leg press 45°. The volunteers performed all tests and the RT session in 3 different conditions: fed state, 12 and 16 hours of IF. The subjective perception of hunger was applied through an adapted visual analogue scale (adVAS). The results showed that strength and power variables did not change significantly: MVIC ( p = 0.960), CMJ ( p = 0.986), MNR back squat ( p = 0.856), MNR leg press 45° ( p = 0.998), TVL ( p = 0.954). However, hunger was significantly greater after the 16-hour fasting ( p = 0.001) compared to 12 hours of fasting and the fed state. Also, the desire to eat was greater after 16 hours ( p = 0.001) compared to 12 hours of fasting and the fed state. This study indicates that IF for 12 or 16 hours does not significantly impair strength and power, but the longer the fasting duration, the greater are the hunger and desire to eat.